Event generator tunes obtained from underlying event and multiparton scattering measurements - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Eroe, J.; Flechl, M.; Ivanov, Andrew; et al. (My University, 2016)
New sets of parameters ("tunes")for the underlying-event (UE) modelling of the PYTHIA8, PYTHIA6 and HERWIG++ MonteCarlo event generators are constructed using different parton distribution functions. Combined fits to CMS UE proton-proton (pp) data at root s = 7 TeV and to UE proton-antiproton (p (P) over bar) data from the CDF experiment at lower root s, are used to study the UE models and constrain their parameters, providing thereby improved predictions for proton-proton collisions at 13 TeV. In addition, it is investigated whether the values of the parameters obtained from fits to UE observables are consistent with the values determined from fitting observables sensitive to double-parton scattering processes. Finally, comparisons are presented of the UE tunes to "minimum bias" (MB) events, multijet, and Drell-Yan (q (Q) over bar -> Z/gamma* -> lepton-antilepton+jets) observables at 7 and 8 TeV, as well as predictions for MB and UE observables at 13 TeV.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Event generator tunes obtained from underlying event and multiparton scattering measurements. European Physical Journal C, 76(3), 52. doi:10.1140/epjc/s10052-016-3988-x
Additional Authors: Friedl, M.;Fruhwirth, R.;Ghete, V. M.;Hartl, C.;Hormann, N.;Hrubec, J.;Jeitler, M.;Knunz, V.;Konig, A.;Krammer, M.;Kratschmer, I.;Liko, D.;Matsushita, T.;Mikulec, I.;Rabady, D.;Rahbaran, B.;Rohringer, H.;Schieck, J.;Schofbeck, R.;Strauss, J.;Treberer-Treberspurg, W.;Waltenberger, W.;Wulz, C. E.;Mossolov, V.;Shumeiko, N.;Gonzalez, J. S.;Alderweireldt, S.;Cornelis, T.;De Wolf, E. A.;Janssen, X.;Knutsson, A.;Lauwers, J.;Luyckx, S.;De Klundert, M. V.;Van Haevermaet, H.;Van Mechelen, P.;Van Remortel, N.;Van Spilbeeck, A.;Abu Zeid, S.;Blekman, F.;D'Hondt, J.;Daci, N.;De Bruyn, I.;Deroover, K.;Heracleous, N.;Keaveney, J.;Lowette, S.;Moreels, L.;Olbrechts, A.;Python, Q.;Strom, D.;Tavernier, S.;Van Doninck, W.;Van Mulders, P.;Van Onsem, G. P.;Van Parijs, I.;Barria, P.;Brun, H.;Caillol, C.;Clerbaux, B.;De Lentdecker, G.;Fasanella, G.;Favart, L.;Grebenyuk, A.;Karapostoli, G.;Lenzi, T.;Leonard, A.;Maerschalk, T.;Marinov, A.;Pernie, L.;Randle-Conde, A.;Seva, T.;Velde, C. V.;Vanlaer, P.;Yonamine, R.;Zenoni, F.;Zhang, F.;Beernaert, K.;Benucci, L.;Cimmino, A.;Crucy, S.;Dobur, D.;Fagot, A.;Garcia, G.;Gul, M.;McCartin, J.;Rios, A. A. O.;Poyraz, D.;Ryckbosch, D.;Salva, S.;Sigamani, M.;Tytgat, M.;Van Driessche, W.;Yazgan, E.;Zaganidis, N.;Basegmez, S.;Beluffi, C.;Bondu, O.;Brochet, S.;Bruno, G.;Caudron, A.;Ceard, L.;Da Silveira, G. G.;Delaere, C.;Favart, D.;Forthomme, L.;Giammanco, A.;Hollar, J.;Jafari, A.;Jez, P.;Komm, M.;Lemaitre, V.;Mertens, A.;Musich, M.;Nuttens, C.;Perrini, L.;Pin, A.;Piotrzkowski, K.;Popov, A.;Quertenmont, L.;Selvaggi, M.;Marono, M. V.;Beliy, N.;Hammad, G. H.;Alda, W. L.;Alves, F. L.;Alves, G. A.;Brito, L.;Martins, M. C.;Hamer, M.;Hensel, C.;Moraes, A.;Pol, M. E.;Teles, P. R.;Das Chagas, E. B. B.;Carvalho, W.;Chinellato, J.;Custodio, A.;Da Costa, E. M.;Damiao, D. D.;Martins, C. D.;Souza, S. F.;Guativa, L. M. H.;Malbouisson, H.;Figueiredo, D. M.;Herrera, C. M.;Mundim, L.;Nogima, H.;Da Silva, W. L. P.;Santoro, A.;Sznajder, A.;Manganote, E. J. T.;Pereira, A. V.;Ahuja, S.;Bernardes, C. A.;Santos, A. D.;Dogra, S.;Tomei, Trfp;Gregores, E. M.;Mercadante, P. G.;Moon, C. S.;Novaes, S. F.;Padula, S. S.;Abad, D. R.;Vargas, J. C. R.;Aleksandrov, A.;Hadjiiska, R.;Iaydjiev, P.;Rodozov, M.;Stoykova, S.;Sultanov, G.;Vutova, M.;Dimitrov, A.;Glushkov, I.;Litov, L.;Pavlov, B.;Petkov, P.;Ahmad, M.;Bian, J. G.;Chen, G. M.;Chen, H. S.;Chen, M.;Cheng, T.;Du, R.;Jiang, C. H.;Plestina, R.;Romeo, F.;Shaheen, S. M.;Spiezia, A.;Tao, J.;Wang, C.;Wang, Z.;Zhang, H.;Asawatangtrakuldee, C.;Ban, Y.;Li, Q.;Liu, S.;Mao, Y.;Qian, S. J.;Wang, D.;Xu, Z.;Avila, C.;Cabrera, A.;Sierra, L. F. C.;Florez, C.;Gomez, J. P.;Moreno, B. G.;Sanabria, J. C.;Godinovic, N.;Lelas, D.;Puljak, I.;Cipriano, P. M. R.;Antunovic, Z.;Kovac, M.;Brigljevic, V.;Kadija, K.;Luetic, J.;Micanovic, S.;Sudic, L.;Attikis, A.;Mavromanolakis, G.;Mousa, J.;Nicolaou, C.;Ptochos, F.;Razis, P. A.;Rykaczewski, H.;Bodlak, M.;Finger, M.;Finger, M.;Abdelalim, A. A.;Awad, A.;Mahrous, A.;Mohammed, Y.;Radi, A.;Calpas, B.;Kadastik, M.;Murumaa, M.;Raidal, M.;Tiko, A.;Veelken, C.;Eerola, P.;Pekkanen, J.;Voutilainen, M.;Harkonen, J.;Karimaki, V.;Kinnunen, R.;Lampen, T.;Lassila-Perini, K.;Lehti, S.;Linden, T.;Luukka, P.;Maenpaa, T.;Peltola, T.;Tuominen, E.;Tuominiemi, J.;Tuovinen, E.;Wendland, L.;Talvitie, J.;Tuuva, T.;Besancon, M.;Couderc, F.;Dejardin, M.;Denegri, D.;Fabbro, B.;Faure, J. L.;Favaro, C.;Ferri, F.;Ganjour, S.;Givernaud, A.;Gras, P.;de Monchenault, G. H.;Jarry, P.;Locci, E.;Machet, M.;Malcles, J.;Rander, J.;Rosowsky, A.;Titov, M.;Zghiche, A.;Antropov, I.;Baffioni, S.;Beaudette, F.;Busson, P.;Cadamuro, L.;Chapon, E.;Charlot, C.;Dahms, T.;Davignon, O.;Filipovic, N.;de Cassagnac, R. G.;Jo, M.;Lisniak, S.;Mastrolorenzo, L.;Mine, P.;Naranjo, I. N.;Nguyen, M.;Ochando, C.;Ortona, G.;Paganini, P.;Pigard, P.;Regnard, S.;Salerno, R.;Sauvan, J. B.;Sirois, Y.;Strebler, T.;Yilmaz, Y.;Zabi, A.;Agram, J. L.;Andrea, J.;Aubin, A.;Bloch, D.;Brom, J. M.;Buttignol, M.;Chabert, E. C.;Chanon, N.;Collard, C.;Conte, E.;Coubez, X.;Fontaine, J. C.;Gele, D.;Goerlach, U.;Goetzmann, C.;Le Bihan, A. C.;Merlin, J. A.;Skovpen, K.;Van Hove, P.;Gadrat, S.;Beauceron, S.;Bernet, C.;Boudoul, G.;Bouvier, E.;Montoya, C. A. C.;Chierici, R.;Contardo, D.;Courbon, B.;Depasse, P.;El Mamouni, H.;Fan, J.;Fay, J.;Gascon, S.;Gouzevitch, M.;Ille, B.;Lagarde, F.;Laktineh, I. B.;Lethuillier, M.;Mirabito, L.;Pequegnot, A. L.;Perries, S.;Alvarez, J. D. R.;Sabes, D.;Sgandurra, L.;Sordini, V.;Donckt, M. V.;Verdier, P.;Viret, S.;Toriashvili, T.;Lomidze, D.;Autermann, C.;Beranek, S.;Edelhoff, M.;Feld, L.;Heister, A.;Kiesel, M. K.;Klein, K.;Lipinski, M.;Ostapchuk, A.;Preuten, M.;Raupach, F.;Schael, S.;Schulte, J. F.;Verlage, T.;Weber, H.;Wittmer, B.;Zhukov, V.;Ata, M.;Brodski, M.;Dietz-Laursonn, E.;Duchardt, D.;Endres, M.;Erdmann, M.;Erdweg, S.;Esch, T.;Fischer, R.;Guth, A.;Hebbeker, T.;Heidemann, C.;Hoepfner, K.;Knutzen, S.;Kreuzer, P.;Merschmeyer, M.;Meyer, A.;Millet, P.;Olschewski, M.;Padeken, K.;Papacz, P.;Pook, T.;Radziej, M.;Reithler, H.;Rieger, M.;Scheuch, F.;Sonnenschein, L.;Teyssier, D.;Thuer, S.;Cherepanov, V.;Erdogan, Y.;Flugge, G.;Geenen, H.;Geisler, M.;Hoehle, F.;Kargoll, B.;Kress, T.;Kuessel, Y.;Kunsken, A.;Lingemann, J.;Nehrkorn, A.;Nowack, A.;Nugent, I. M.;Pistone, C.;Pooth, O.;Stahl, A.;Martin, M. A.;Asin, I.;Bartosik, N.;Behnke, O.;Behrens, U.;Bell, A. J.;Borras, K.;Burgmeier, A.;Campbell, A.;Choudhury, S.;Costanza, F.;Pardos, C. D.;Dolinska, G.;Dooling, S.;Dorland, T.;Eckerlin, G.;Eckstein, D.;Eichhorn, T.;Flucke, G.;Gallo, E.;Garcia, J. G.;Geiser, A.;Gizhko, A.;Gunnellini, P.;Hauk, J.;Hempel, M.;Jung, H.;Kalogeropoulos, A.;Karacheban, O.;Kasemann, M.;Katsas, P.;Kieseler, J.;Kleinwort, C.;Korol, I.;Lange, W.;Leonard, J.;Lipka, K.;Lobanov, A.;Lohmann, W.;Mankel, R.;Marfin, I.;Melzer-Pellmann, I. A.;Meyer, A. B.;Mittag, G.;Mnich, J.;Mussgiller, A.;Naumann-Emme, S.;Nayak, A.;Ntomari, E.;Perrey, H.;Pitzl, D.;Placakyte, R.;Raspereza, A.;Roland, B.;Sahin, M. O.;Saxena, P.;Schoerner-Sadenius, T.;Schroder, M.;Seitz, C.;Spannagel, S.;Trippkewitz, K. D.;Walsh, R.;Wissing, C.;Blobel, V.;Vignali, M. C.;Draeger, A. R.;Erfle, J.;Garutti, E.;Goebel, K.;Gonzalez, D.;Gorner, M.;Haller, J.;Hoffmann, M.;Hoing, R. S.;Junkes, A.;Klanner, R.;Kogler, R.;Kovalchuk, N.;Lapsien, T.;Lenz, T.;Marchesini, I.;Marconi, D.;Meyer, M.;Nowatschin, D.;Ott, J.;Pantaleo, F.;Peiffer, T.;Perieanu, A.;Pietsch, N.;Poehlsen, J.;Rathjens, D.;Sander, C.;Scharf, C.;Schettler, H.;Schleper, P.;Schlieckau, E.;Schmidt, A.;Schwandt, J.;Sola, V.;Stadie, H.;Steinbruck, G.;Tholen, H.;Troendle, D.;Usai, E.;Vanelderen, L.;Vanhoefer, A.;Vormwald, B.;Barth, C.;Baus, C.;Berger, J.;Boser, C.;Butz, E.;Chwalek, T.;Colombo, F.;De Boer, W.;Descroix, A.;Dierlamm, A.;Fink, S.;Frensch, F.;Friese, R.;Giffels, M.;Gilbert, A.;Haitz, D.;Hartmann, F.;Heindl, S. M.;Husemann, U.;Katkov, I.;Kornmayer, A.;Pardo, P. L.;Maier, B.;Mildner, H.;Mozer, M. U.;Muller, T.;Muller, T.;Plagge, M.;Quast, G.;Rabbertz, K.;Rocker, S.;Roscher, F.;Sieber, G.;Simonis, H. J.;Stober, F. M.;Ulrich, R.;Wagner-Kuhr, J.;Wayand, S.;Weber, M.;Weiler, T.;Williamson, S.;Wohrmann, C.;Wolf, R.;Anagnostou, G.;Daskalakis, G.;Geralis, T.;Giakoumopoulou, V. A.;Kyriakis, A.;Loukas, D.;Psallidas, A.;Topsis-Giotis, I.;Agapitos, A.;Kesisoglou, S.;Panagiotou, A.;Saoulidou, N.;Tziaferi, E.;Evangelou, I.;Flouris, G.;Foudas, C.;Kokkas, P.;Loukas, N.;Manthos, N.;Papadopoulos, I.;Paradas, E.;Strologas, J.;Bencze, G.;Hajdu, C.;Hazi, A.;Hidas, P.;Horvath, D.;Sikler, F.;Veszpremi, V.;Vesztergombi, G.;Zsigmond, A. J.;Beni, N.;Czellar, S.;Karancsi, J.;Molnar, J.;Szillasi, Z.;Bartok, M.;Makovec, A.;Raics, P.;Trocsanyi, Z. L.;Ujvari, B.;Mal, P.;Mandal, K.;Sahoo, D. K.;Sahoo, N.;Swain, S. K.;Bansal, S.;Beri, S. B.;Bhatnagar, V.;Chawla, R.;Gupta, R.;Bhawandeep, U.;Kalsi, A. K.;Kaur, A.;Kaur, M.;Kumar, R.;Mehta, A.;Mittal, M.;Singh, J. B.;Walia, G.;Kumar, A.;Bhardwaj, A.;Choudhary, B. C.;Garg, R. B.;Kumar, A.;Malhotra, S.;Naimuddin, M.;Nishu, N.;Ranjan, K.;Sharma, R.;Sharma, V.;Bhattacharya, S.;Chatterjee, K.;Dey, S.;Dutta, S.;Jain, S.;Majumdar, N.;Modak, A.;Mondal, K.;Mukherjee, S.;Mukhopadhyay, S.;Roy, A.;Roy, D.;Chowdhury, S. R.;Sarkar, S.;Sharan, M.;Abdulsalam, A.;Chudasama, R.;Dutta, D.;Jha, V.;Kumar, V.;Mohanty, A. K.;Pant, L. M.;Shukla, P.;Topkar, A.;Aziz, T.;Banerjee, S.;Bhowmik, S.;Chatterjee, R. M.;Dewanjee, R. K.;Dugad, S.;Ganguly, S.;Ghosh, S.;Guchait, M.;Gurtu, A.;Kole, G.;Kumar, S.;Mahakud, B.;Maity, M.;Majumder, G.;Mazumdar, K.;Mitra, S.;Mohanty, G. B.;Parida, B.;Sarkar, T.;Sur, N.;Sutar, B.;Wickramage, N.;Chauhan, S.;Dube, S.;Kapoor, A.;Kothekar, K.;Sharma, S.;Bakhshiansohi, H.;Behnamian, H.;Etesami, S. M.;Fahim, A.;Goldouzian, R.;Khakzad, M.;Najafabadi, M. M.;Naseri, M.;Mehdiabadi, S. P.;Hosseinabadi, F. R.;Safarzadeh, B.;Zeinali, M.;Felcini, M.;Grunewald, M.;Abbrescia, M.;Calabria, C.;Caputo, C.;Colaleo, A.;Creanza, D.;Cristella, L.;De Filippis, N.;De Palma, M.;Fiore, L.;Iaselli, G.;Maggi, G.;Maggi, M.;Miniello, G.;My, S.;Nuzzo, S.;Pompili, A.;Pugliese, G.;Radogna, R.;Ranieri, A.;Selvaggi, G.;Silvestris, L.;Venditti, R.;Verwilligen, P.;Abbiendi, G.;Battilana, C.;Benvenuti, A. C.;Bonacorsi, D.;Braibant-Giacomelli, S.;Brigliadori, L.;Campanini, R.;Capiluppi, P.;Castro, A.;Cavallo, F. R.;Chhibra, S. S.;Codispoti, G.;Cuffiani, M.;Dallavalle, G. M.;Fabbri, F.;Fanfani, A.;Fasanella, D.;Giacomelli, P.;Grandi, C.;Guiducci, L.;Marcellini, S.;Masetti, G.;Montanari, A.;Navarria, F. L.;Perrotta, A.;Rossi, A. M.;Rovelli, T.;Siroli, G. P.;Tosi, N.;Travaglini, R.;Cappello, G.;Chiorboli, M.;Costa, S.;Di Mattia, A.;Giordano, F.;Potenza, R.;Tricomi, A.;Tuve, C.;Barbagli, G.;Ciulli, V.;Civinini, C.;D'Alessandro, R.;Focardi, E.;Gonzi, S.;Gori, V.;Lenzi, P.;Meschini, M.;Paoletti, S.;Sguazzoni, G.;Tropiano, A.;Viliani, L.;Benussi, L.;Bianco, S.;Fabbri, F.;Piccolo, D.;Primavera, F.;Calvelli, V.;Ferro, F.;Lo Vetere, M.;Monge, M. R.;Robutti, E.;Tosi, S.;Brianza, L.;Dinardo, M. E.;Fiorendi, S.;Gennai, S.;Gerosa, R.;Ghezzi, A.;Govoni, P.;Malvezzi, S.;Manzoni, R. A.;Marzocchi, B.;Menasce, D.;Moroni, L.;Paganoni, M.;Pedrini, D.;Ragazzi, S.;Redaelli, N.;de Fatis, T. T.;Buontempo, S.;Cavallo, N.;Di Guida, S.;Esposito, M.;Fabozzi, F.;Iorio, A. O. M.;Lanza, G.;Lista, L.;Meola, S.;Merola, M.;Paolucci, P.;Sciacca, C.;Thyssen, F.;Azzi, P.;Bacchetta, N.;Benato, L.;Bisello, D.;Boletti, A.;Branca, A.;Carlin, R.;Checchia, P.;Dall'Osso, M.;Dorigo, T.;Dosselli, U.;Fantinel, S.;Fanzago, F.;Gasparini, F.;Gasparini, U.;Gozzelino, A.;Kanishchev, K.;Lacaprara, S.;Margoni, M.;Meneguzzo, A. T.;Pazzini, J.;Pozzobon, N.;Ronchese, P.;Simonetto, F.;Torassa, E.;Tosi, M.;Zanetti, M.;Zotto, P.;Zucchetta, A.;Braghieri, A.;Magnani, A.;Montagna, P.;Ratti, S. P.;Re, V.;Riccardi, C.;Salvini, P.;Vai, I.;Vitulo, P.;Solestizi, L. A.;Bilei, G. M.;Ciangottini, D.;Fano, L.;Lariccia, P.;Mantovani, G.;Menichelli, M.;Saha, A.;Santocchia, A.;Androsov, K.;Azzurri, P.;Bagliesi, G.;Bernardini, J.;Boccali, T.;Castaldi, R.;Ciocci, M. A.;Dell'Orso, R.;Donato, S.;Fedi, G.;Foa, L.;Giassi, A.;Grippo, M. T.;Ligabue, F.;Lomtadze, T.;Martini, L.;Messineo, A.;Palla, F.;Rizzi, A.;Savoy-Navarro, A.;Serban, A. T.;Spagnolo, P.;Tenchini, R.;Tonelli, G.;Venturi, A.;Verdini, P. G.;Barone, L.;Cavallari, F.;D'Imperio, G.;Del Re, D.;Diemoz, M.;Gelli, S.;Jorda, C.;Longo, E.;Margaroli, F.;Meridiani, P.;Organtini, G.;Paramatti, R.;Preiato, F.;Rahatlou, S.;Rovelli, C.;Santanastasio, F.;Traczyk, P.;Amapane, N.;Arcidiacono, R.;Argiro, S.;Arneodo, M.;Bellan, R.;Biino, C.;Cartiglia, N.;Costa, M.;Covarelli, R.;Degano, A.;Demaria, N.;Finco, L.;Kiani, B.;Mariotti, C.;Maselli, S.;Migliore, E.;Monaco, V.;Monteil, E.;Obertino, M. M.;Pacher, L.;Pastrone, N.;Pelliccioni, M.;Angioni, G. L. P.;Ravera, F.;Romero, A.;Ruspa, M.;Sacchi, R.;Solano, A.;Staiano, A.;Belforte, S.;Candelise, V.;Casarsa, M.;Cossutti, F.;Della Ricca, G.;Gobbo, B.;La Licata, C.;Marone, M.;Schizzi, A.;Zanetti, A.;Kropivnitskaya, A.;Nam, S. K.;Kim, D. H.;Kim, G. N.;Kim, M. S.;Kong, D. J.;Lee, S.;Oh, Y. D.;Sakharov, A.;Son, D. C.;Cifuentes, J. A. B.;Kim, H.;Kim, T. J.;Song, S.;Choi, S.;Go, Y.;Gyun, D.;Hong, B.;Kim, H.;Kim, Y.;Lee, B.;Lee, K.;Lee, K. S.;Lee, S.;Park, S. K.;Roh, Y.;Yoo, H. D.;Choi, M.;Kim, H.;Kim, J. H.;Lee, J. S. H.;Park, I. C.;Ryu, G.;Ryu, M. S.;Choi, Y.;Goh, J.;Kim, D.;Kwon, E.;Lee, J.;Yu, I.;Dudenas, V.;Juodagalvis, A.;Vaitkus, J.;Ahmed, I.;Ibrahim, Z. A.;Komaragiri, J. R.;Ali, Mabm;Idris, F. M.;Abdullah, Watw;Yusli, M. N.;Linares, E. C.;Castilla-Valdez, H.;De la Cruz-Burelo, E.;Heredia-De la Cruz, I.;Hernandez-Almada, A.;Lopez-Fernandez, R.;Sanchez-Hernandez, A.;Moreno, S. C.;Valencia, F. V.;Pedraza, I.;Ibarguen, H. A. S.;Pineda, A. M.;Krofcheck, D.;Butler, P. H.;Ahmad, A.;Ahmad, M.;Hassan, Q.;Hoorani, H. R.;Khan, W. A.;Khurshid, T.;Shoaib, M.;Bialkowska, H.;Bluj, M.;Boimska, B.;Frueboes, T.;Gorski, M.;Kazana, M.;Nawrocki, K.;Romanowska-Rybinska, K.;Szleper, M.;Zalewski, P.;Brona, G.;Bunkowski, K.;Byszuk, A.;Doroba, K.;Kalinowski, A.;Konecki, M.;Krolikowski, J.;Misiura, M.;Olszewski, M.;Walczak, M.;Bargassa, P.;Silva, Cbde;Di Francesco, A.;Faccioli, P.;Parracho, P. G. F.;Gallinaro, M.;Leonardo, N.;Iglesias, L. L.;Nguyen, F.;Antunes, J. R.;Seixas, J.;Toldaiev, O.;Vadruccio, D.;Varela, J.;Vischia, P.;Afanasiev, S.;Bunin, P.;Gavrilenko, M.;Golutvin, I.;Gorbunov, I.;Kamenev, A.;Karjavin, V.;Konoplyanikov, V.;Lanev, A.;Malakhov, A.;Matveev, V.;Moisenz, P.;Palichik, V.;Perelygin, V.;Shmatov, S.;Shulha, S.;Skatchkov, N.;Smirnov, V.;Zarubin, A.;Golovtsov, V.;Ivanov, Y.;Kim, V.;Kuznetsova, E.;Levchenko, P.;Murzin, V.;Oreshkin, V.;Smirnov, I.;Sulimov, V.;Uvarov, L.;Vavilov, S.;Vorobyev, A.;Andreev, Y.;Dermenev, A.;Gninenko, S.;Golubev, N.;Karneyeu, A.;Kirsanov, M.;Krasnikov, N.;Pashenkov, A.;Tlisov, D.;Toropin, A.;Epshteyn, V.;Gavrilov, V.;Lychkovskaya, N.;Popov, V.;Pozdnyakov, I.;Safronov, G.;Spiridonov, A.;Vlasov, E.;Zhokin, A.;Bylinkin, A.;Andreev, V.;Azarkin, M.;Dremin, I.;Kirakosyan, M.;Leonidov, A.;Mesyats, G.;Rusakov, S. V.;Baskakov, A.;Belyaev, A.;Boos, E.;Dubinin, M.;Dudko, L.;Ershov, A.;Gribushin, A.;Klyukhin, V.;Kodolova, O.;Lokhtin, I.;Myagkov, I.;Obraztsov, S.;Petrushanko, S.;Savrin, V.;Snigirev, A.;Azhgirey, I.;Bayshev, I.;Bitioukov, S.;Kachanov, V.;Kalinin, A.;Konstantinov, D.;Krychkine, V.;Petrov, V.;Ryutin, R.;Sobol, A.;Tourtchanovitch, L.;Troshin, S.;Tyurin, N.;Uzunian, A.;Volkov, A.;Adzic, P.;Cirkovic, P.;Milosevic, J.;Rekovic, V.;Maestre, J. A.;Calvo, E.;Cerrada, M.;Llatas, M. C.;Colino, N.;De la Cruz, B.;Peris, A. D.;Del Valle, A. E.;Bedoya, C. F.;Ramos, J. P. F.;Flix, J.;Fouz, M. C.;Garcia-Abia, P.;Lopez, O. G.;Lopez, S. G.;Hernandez, J. M.;Josa, M. I.;De Martino, E. N.;Yzquierdo, A. P. C.;Pelayo, J. P.;Olmeda, A. Q.;Redondo, I.;Romero, L.;Santaolalla, J.;Soares, M. S.;Albajar, C.;de Troconiz, J. F.;Missiroli, M.;Moran, D.;Cuevas, J.;Menendez, J. F.;Folgueras, S.;Caballero, I. G.;Cortezon, E. P.;Garcia, J. M. V.;Cabrillo, I. J.;Calderon, A.;Saa, J. R. C.;Manzano, P. D.;Fernandez, M.;Garcia-Ferrero, J.;Gomez, G.;Virto, A. L.;Marco, J.;Marco, R.;Rivero, C. M.;Matorras, F.;Gomez, J. P.;Rodrigo, T.;Rodriguez-Marrero, A. Y.;Ruiz-Jimeno, A.;Scodellaro, L.;Trevisani, N.;Vila, I.;Cortabitarte, R. V.;Abbaneo, D.;Auffray, E.;Auzinger, G.;Bachtis, M.;Baillon, P.;Ball, A. H.;Barney, D.;Benaglia, A.;Bendavid, J.;Benhabib, L.;Benitez, J. F.;Berruti, G. M.;Bloch, P.;Bocci, A.;Bonato, A.;Botta, C.;Breuker, H.;Camporesi, T.;Castello, R.;Cerminara, G.;D'Alfonso, M.;d'Enterria, D.;Dabrowski, A.;Daponte, V.;David, A.;De Gruttola, M.;De Guio, F.;De Roeck, A.;De Visscher, S.;Di Marco, E.;Dobson, M.;Dordevic, M.;Dorney, B.;du Pree, T.;Duggan, D.;Dunser, M.;Dupont, N.;Elliott-Peisert, A.;Franzoni, G.;Fulcher, J.;Funk, W.;Gigi, D.;Gill, K.;Giordano, D.;Girone, M.;Glege, F.;Guida, R.;Gundacker, S.;Guthoff, M.;Hammer, J.;Harris, P.;Hegeman, J.;Innocente, V.;Janot, P.;Kirschenmann, H.;Kortelainen, M. J.;Kousouris, K.;Krajczar, K.;Lecoq, P.;Lourenco, C.;Lucchini, M. T.;Magini, N.;Malgeri, L.;Mannelli, M.;Martelli, A.;Masetti, L.;Meijers, F.;Mersi, S.;Meschi, E.;Moortgat, F.;Morovic, S.;Mulders, M.;Nemallapudi, M. V.;Neugebauer, H.;Orfanelli, S.;Orsini, L.;Pape, L.;Perez, E.;Peruzzi, M.;Petrilli, A.;Petrucciani, G.;Pfeiffer, A.;Piparo, D.;Racz, A.;Reis, T.;Rolandi, G.;Rovere, M.;Ruan, M.;Sakulin, H.;Schafer, C.;Schwick, C.;Seidel, M.;Sharma, A.;Silva, P.;Simon, M.;Sphicas, P.;Steggemann, J.;Stieger, B.;Stoye, M.;Takahashi, Y.;Treille, D.;Triossi, A.;Tsirou, A.;Veres, G. I.;Wardle, N.;Wohri, H. K.;Zagozdzinska, A.;Zeuner, W. D.;Bertl, W.;Deiters, K.;Erdmann, W.;Horisberger, R.;Ingram, Q.;Kaestli, H. C.;Kotlinski, D.;Langenegger, U.;Renker, D.;Rohe, T.;Bachmair, F.;Bani, L.;Bianchini, L.;Casal, B.;Dissertori, G.;Dittmar, M.;Donega, M.;Eller, P.;Grab, C.;Heidegger, C.;Hits, D.;Hoss, J.;Kasieczka, G.;Lustermann, W.;Mangano, B.;Marionneau, M.;del Arbol, P. M. R.;Masciovecchio, M.;Meister, D.;Micheli, F.;Musella, P.;Nessi-Tedaldi, F.;Pandolfi, F.;Pata, J.;Pauss, F.;Perrozzi, L.;Quittnat, M.;Rossini, M.;Starodumov, A.;Takahashi, M.;Tavolaro, V. R.;Theofilatos, K.;Wallny, R.;Aarrestad, T. K.;Amsler, C.;Caminada, L.;Canelli, M. F.;Chiochia, V.;De Cosa, A.;Galloni, C.;Hinzmann, A.;Hreus, T.;Kilminster, B.;Lange, C.;Ngadiuba, J.;Pinna, D.;Robmann, P.;Ronga, F. J.;Salerno, D.;Yang, Y.;Cardaci, M.;Chen, K. H.;Doan, T. H.;Jain, S.;Khurana, R.;Konyushikhin, M.;Kuo, C. M.;Lin, W.;Lu, Y. J.;Yu, S. S.;Kumar, A.;Bartek, R.;Chang, P.;Chang, Y. H.;Chang, Y. W.;Chao, Y.;Chen, K. F.;Chen, P. H.;Dietz, C.;Fiori, F.;Grundler, U.;Hou, W. S.;Hsiung, Y.;Liu, Y. F.;Lu, R. S.;Moya, M. M.;Petrakou, E.;Tsai, J. F.;Tzeng, Y. M.;Asavapibhop, B.;Kovitanggoon, K.;Singh, G.;Srimanobhas, N.;Suwonjandee, N.;Adiguzel, A.;Bakirci, M. N.;Cerci, S.;Demiroglu, Z. S.;Dozen, C.;Eskut, E.;Gecit, F. H.;Girgis, S.;Gokbulut, G.;Guler, Y.;Gurpinar, E.;Hos, I.;Kangal, E. E.;Onengut, G.;Ozcan, M.;Ozdemir, K.;Polatoz, A.;Cerci, D. S.;Topakli, H.;Vergili, M.;Zorbilmez, C.;Akin, I. V.;Bilin, B.;Bilmis, S.;Isildak, B.;Karapinar, G.;Yalvac, M.;Zeyrek, M.;Gulmez, E.;Kaya, M.;Kaya, O.;Yetkin, E. A.;Yetkin, T.;Cakir, A.;Cankocak, K.;Sen, S.;Vardarli, F. I.;Grynyov, B.;Levchuk, L.;Sorokin, P.;Aggleton, R.;Ball, F.;Beck, L.;Brooke, J. J.;Clement, E.;Cussans, D.;Flacher, H.;Goldstein, J.;Grimes, M.;Heath, G. P.;Heath, H. F.;Jacob, J.;Kreczko, L.;Lucas, C.;Meng, Z.;Newbold, D. M.;Paramesvaran, S.;Poll, A.;Sakuma, T.;El Nasr-storey, S. S.;Senkin, S.;Smith, D.;Smith, V. J.;Bell, K. W.;Belyaev, A.;Brew, C.;Brown, R. M.;Calligaris, L.;Cieri, D.;Cockerill, D. J. A.;Coughlan, J. A.;Harder, K.;Harper, S.;Olaiya, E.;Petyt, D.;Shepherd-Themistocleous, C. H.;Thea, A.;Tomalin, I. R.;Williams, T.;Worm, S. D.;Baber, M.;Bainbridge, R.;Buchmuller, O.;Bundock, A.;Burton, D.;Casasso, S.;Citron, M.;Colling, D.;Corpe, L.;Cripps, N.;Dauncey, P.;Davies, G.;De Wit, A.;Della Negra, M.;Dunne, P.;Elwood, A.;Ferguson, W.;Futyan, D.;Hall, G.;Iles, G.;Kenzie, M.;Lane, R.;Lucas, R.;Lyons, L.;Magnan, A. M.;Malik, S.;Nash, J.;Nikitenko, A.;Pela, J.;Pesaresi, M.;Petridis, K.;Raymond, D. M.;Richards, A.;Rose, A.;Seez, C.;Tapper, A.;Uchida, K.;Acosta, M. V.;Virdee, T.;Zenz, S. C.;Cole, J. E.;Hobson, P. R.;Khan, A.;Kyberd, P.;Leggat, D.;Leslie, D.;Reid, I. D.;Symonds, P.;Teodorescu, L.;Turner, M.;Borzou, A.;Call, K.;Dittmann, J.;Hatakeyama, K.;Liu, H.;Pastika, N.;Charaf, O.;Cooper, S. I.;Henderson, C.;Rumerio, P.;Arcaro, D.;Avetisyan, A.;Bose, T.;Fantasia, C.;Gastler, D.;Lawson, P.;Rankin, D.;Richardson, C.;Rohlf, J.;St John, J.;Sulak, L.;Zou, D.;Alimena, J.;Berry, E.;Bhattacharya, S.;Cutts, D.;Dhingra, N.;Ferapontov, A.;Garabedian, A.;Hakala, J.;Heintz, U.;Laird, E.;Landsberg, G.;Mao, Z.;Narain, M.;Piperov, S.;Sagir, S.;Syarif, R.;Breedon, R.;Breto, G.;Sanchez, M. C. D.;Chauhan, S.;Chertok, M.;Conway, J.;Conway, R.;Cox, P. T.;Erbacher, R.;Funk, G.;Gardner, M.;Ko, W.;Lander, R.;Mulhearn, M.;Pellett, D.;Pilot, J.;Ricci-Tam, F.;Shalhout, S.;Smith, J.;Squires, M.;Stolp, D.;Tripathi, M.;Wilbur, S.;Yohay, R.;Bravo, C.;Cousins, R.;Everaerts, P.;Farrell, C.;Florent, A.;Hauser, J.;Ignatenko, M.;Saltzberg, D.;Schnaible, C.;Takasugi, E.;Valuev, V.;Weber, M.;Burt, K.;Clare, R.;Ellison, J.;Gary, J. W.;Hanson, G.;Heilman, J.;Paneva, M. I.;Jandir, P.;Kennedy, E.;Lacroix, F.;Long, O. R.;Luthra, A.;Malberti, M.;Negrete, M. O.;Shrinivas, A.;Wei, H.;Wimpenny, S.;Yates, B. R.;Branson, J. G.;Cerati, G. B.;Cittolin, S.;D'Agnolo, R. T.;Derdzinski, M.;Holzner, A.;Kelley, R.;Klein, D.;Letts, J.;Macneill, I.;Olivito, D.;Padhi, S.;Pieri, M.;Sani, M.;Sharma, V.;Simon, S.;Tadel, M.;Vartak, A.;Wasserbaech, S.;Welke, C.;Wurthwein, F.;Yagil, A.;Della Porta, G. Z.;Bradmiller-Feld, J.;Campagnari, C.;Dishaw, A.;Dutta, V.;Flowers, K.;Sevilla, M. F.;Geffert, P.;George, C.;Golf, F.;Gouskos, L.;Incandela, J. G. J.;McColl, N.;Mullin, S. D.;Richman, J.;Stuart, D.;Suarez, I.;West, C.;Yoo, J.;Anderson, D.;Apresyan, A.;Bornheim, A.;Bunn, J.;Chen, Y.;Duarte, J.;Mott, A.;Newman, H. B.;Pena, C.;Pierini, M.;Spiropulu, M.;Vlimant, J. R.;Xie, S.;Zhu, R. Y.;Andrews, M. B.;Azzolini, V.;Calamba, A.;Carlson, B.;Ferguson, T.;Paulini, M.;Russ, J.;Sun, M.;Vogel, H.;Vorobiev, I.;Cumalat, J. P.;Ford, W. T.;Gaz, A.;Jensen, F.;Johnson, A.;Krohn, M.;Mulholland, T.;Nauenberg, U.;Stenson, K.;Wagner, S. R.;Alexander, J.;Chatterjee, A.;Chaves, J.;Chu, J.;Dittmer, S.;Eggert, N.;Mirman, N.;Kaufman, G. N.;Patterson, J. R.;Rinkevicius, A.;Ryd, A.;Skinnari, L.;Soffi, L.;Sun, W.;Tan, S. M.;Teo, W. D.;Thom, J.;Thompson, J.;Tucker, J.;Weng, Y.;Wittich, P.;Abdullin, S.;Albrow, M.;Apollinari, G.;Banerjee, S.;Bauerdick, L. A. T.;Beretvas, A.;Berryhill, J.;Bhat, P. C.;Bolla, G.;Burkett, K.;Butler, J. N.;Cheung, H. W. K.;Chlebana, F.;Cihangir, S.;Elvira, V. D.;Fisk, I.;Freeman, J.;Gottschalk, E.;Gray, L.;Green, D.;Grunendahl, S.;Gutsche, O.;Hanlon, J.;Hare, D.;Harris, R. M.;Hasegawa, S.;Hirschauer, J.;Hu, Z.;Jayatilaka, B.;Jindariani, S.;Johnson, M.;Joshi, U.;Jung, A. W.;Klima, B.;Kreis, B.;Lammel, S.;Linacre, J.;Lincoln, D.;Lipton, R.;Liu, T.;De Sa, R. L.;Lykken, J.;Maeshima, K.;Marraffino, J. M.;Outschoorn, V. I. M.;Maruyama, S.;Mason, D.;McBride, P.;Merkel, P.;Mishra, K.;Mrenna, S.;Nahn, S.;Newman-Holmes, C.;O'Dell, V.;Pedro, K.;Prokofyev, O.;Rakness, G.;Sexton-Kennedy, E.;Soha, A.;Spalding, W. J.;Spiegel, L.;Strobbe, N.;Taylor, L.;Tkaczyk, S.;Tran, N. V.;Uplegger, L.;Vaandering, E. W.;Vernieri, C.;Verzocchi, M.;Vidal, R.;Weber, H. A.;Whitbeck, A.;Acosta, D.;Avery, P.;Bortignon, P.;Bourilkov, D.;Carnes, A.;Carver, M.;Curry, D.;Das, S.;Field, R. D.;Furic, I. K.;Gleyzer, S. V.;Hugon, J.;Konigsberg, J.;Korytov, A.;Kotov, K.;Low, J. F.;Ma, P.;Matchev, K.;Mei, H.;Milenovic, P.;Mitselmakher, G.;Rank, D.;Rossin, R.;Shchutska, L.;Snowball, M.;Sperka, D.;Terentyev, N.;Thomas, L.;Wang, J.;Wang, S.;Yelton, J.;Hewamanage, S.;Linn, S.;Markowitz, P.;Martinez, G.;Rodriguez, J. L.;Ackert, A.;Adams, J. R.;Adams, T.;Askew, A.;Bein, S.;Bochenek, J.;Diamond, B.;Haas, J.;Hagopian, S.;Hagopian, V.;Johnson, K. F.;Khatiwada, A.;Prosper, H.;Weinberg, M.;Baarmand, M. M.;Bhopatkar, V.;Colafranceschi, S.;Hohlmann, M.;Kalakhety, H.;Noonan, D.;Roy, T.;Yumiceva, F.;Adams, M. R.;Apanasevich, L.;Berry, D.;Betts, R. R.;Bucinskaite, I.;Cavanaugh, R.;Evdokimov, O.;Gauthier, L.;Gerber, C. E.;Hofman, D. J.;Kurt, P.;O'Brien, C.;Gonzalez, I. D. S.;Silkworth, C.;Turner, P.;Varelas, N.;Wu, Z.;Zakaria, M.;Bilki, B.;Clarida, W.;Dilsiz, K.;Durgut, S.;Gandrajula, R. P.;Haytmyradov, M.;Khristenko, V.;Merlo, J. P.;Mermerkaya, H.;Mestvirishvili, A.;Moeller, A.;Nachtman, J.;Ogul, H.;Onel, Y.;Ozok, F.;Penzo, A.;Snyder, C.;Tiras, E.;Wetzel, J.;Yi, K.;Anderson, I.;Barnett, B. A.;Blumenfeld, B.;Eminizer, N.;Fehling, D.;Feng, L.;Gritsan, A. V.;Maksimovic, P.;Martin, C.;Osherson, M.;Roskes, J.;Sady, A.;Sarica, U.;Swartz, M.;Xiao, M.;Xin, Y.;You, C.;Baringer, P.;Bean, A.;Benelli, G.;Bruner, C.;Kennyiii, R. P.;Majumder, D.;Malek, M.;Murray, M.;Sanders, S.;Stringer, R.;Wang, Q.;Ivanov, A.;Kaadze, K.;Khalil, S.;Makouski, M.;Maravin, Y.;Mohammadi, A.;Saini, L. K.;Skhirtladze, N.;Toda, S.;Lange, D.;Rebassoo, F.;Wright, D.;Anelli, C.;Baden, A.;Baron, O.;Belloni, A.;Calvert, B.;Eno, S. C.;Ferraioli, C.;Gomez, J. A.;Hadley, N. J.;Jabeen, S.;Kellogg, R. G.;Kolberg, T.;Kunkle, J.;Lu, Y.;Mignerey, A. C.;Shin, Y. H.;Skuja, A.;Tonjes, M. B.;Tonwar, S. C.;Apyan, A.;Barbieri, R.;Baty, A.;Bierwagen, K.;Brandt, S.;Busza, W.;Cali, I. A.;Demiragli, Z.;Di Matteo, L.;Ceballos, G. G.;Goncharov, M.;Gulhan, D.;Iiyama, Y.;Innocenti, G. M.;Klute, M.;Kovalskyi, D.;Lai, Y. S.;Lee, Y. J.;Levin, A.;Luckey, P. D.;Marini, A. C.;McGinn, C.;Mironov, C.;Narayanan, S.;Niu, X.;Paus, C.;Ralph, D.;Roland, C.;Roland, G.;Salfeld-Nebgen, J.;Stephans, G. S. F.;Sumorok, K.;Varma, M.;Velicanu, D.;Veverka, J.;Wang, J.;Wang, T. W.;Wyslouch, B.;Yang, M.;Zhukova, V.;Dahmes, B.;Evans, A.;Finkel, A.;Gude, A.;Hansen, P.;Kalafut, S.;Kao, S. C.;Klapoetke, K.;Kubota, Y.;Lesko, Z.;Mans, J.;Nourbakhsh, S.;Ruckstuhl, N.;Rusack, R.;Tambe, N.;Turkewitz, J.;Acosta, J. G.;Oliveros, S.;Avdeeva, E.;Bloom, K.;Bose, S.;Claes, D. R.;Dominguez, A.;Fangmeier, C.;Suarez, R. G.;Kamalieddin, R.;Keller, J.;Knowlton, D.;Kravchenko, I.;Meier, F.;Monroy, J.;Ratnikov, F.;Siado, J. E.;Snow, G. R.;Alyari, M.;Dolen, J.;George, J.;Godshalk, A.;Harrington, C.;Iashvili, I.;Kaisen, J.;Kharchilava, A.;Kumar, A.;Rappoccio, S.;Roozbahani, B.;Alverson, G.;Barberis, E.;Baumgartel, D.;Chasco, M.;Hortiangtham, A.;Massironi, A.;Morse, D. M.;Nash, D.;Orimoto, T.;De Lima, R. T.;Trocino, D.;Wang, R. J.;Wood, D.;Zhang, J.;Hahn, K. A.;Kubik, A.;Mucia, N.;Odell, N.;Pollack, B.;Pozdnyakov, A.;Schmitt, M.;Stoynev, S.;Sung, K.;Trovato, M.;Velasco, M.;Brinkerhoff, A.;Dev, N.;Hildreth, M.;Jessop, C.;Karmgard, D. J.;Kellams, N.;Lannon, K.;Marinelli, N.;Meng, F.;Mueller, C.;Musienko, Y.;Planer, M.;Reinsvold, A.;Ruchti, R.;Smith, G.;Taroni, S.;Valls, N.;Wayne, M.;Wolf, M.;Woodard, A.;Antonelli, L.;Brinson, J.;Bylsma, B.;Durkin, L. S.;Flowers, S.;Hart, A.;Hill, C.;Hughes, R.;Ji, W.;Ling, T. Y.;Liu, B.;Luo, W.;Puigh, D.;Rodenburg, M.;Winer, B. L.;Wulsin, H. W.;Driga, O.;Elmer, P.;Hardenbrook, J.;Hebda, P.;Koay, S. A.;Lujan, P.;Marlow, D.;Medvedeva, T.;Mooney, M.;Olsen, J.;Palmer, C.;Piroue, P.;Saka, H.;Stickland, D.;Tully, C.;Zuranski, A.;Malik, S.;Barnes, V. E.;Benedetti, D.;Bortoletto, D.;Gutay, L.;Jha, M. K.;Jones, M.;Jung, K.;Miller, D. H.;Neumeister, N.;Radburn-Smith, B. C.;Shi, X.;Shipsey, I.;Silvers, D.;Sun, J.;Svyatkovskiy, A.;Wang, F.;Xie, W.;Xu, L.;Parashar, N.;Stupak, J.;Adair, A.;Akgun, B.;Chen, Z.;Ecklund, K. M.;Geurts, F. J. M.;Guilbaud, M.;Li, W.;Michlin, B.;Northup, M.;Padley, B. P.;Redjimi, R.;Roberts, J.;Rorie, J.;Tu, Z.;Zabel, J.;Betchart, B.;Bodek, A.;de Barbaro, P.;Demina, R.;Eshaq, Y.;Ferbel, T.;Galanti, M.;Garcia-Bellido, A.;Han, J.;Harel, A.;Hindrichs, O.;Khukhunaishvili, A.;Petrillo, G.;Tan, P.;Verzetti, M.;Arora, S.;Barker, A.;Chou, J. P.;Contreras-Campana, C.;Contreras-Campana, E.;Ferencek, D.;Gershtein, Y.;Gray, R.;Halkiadakis, E.;Hidas, D.;Hughes, E.;Kaplan, S.;Elayavalli, R. K.;Lath, A.;Nash, K.;Panwalkar, S.;Park, M.;Salur, S.;Schnetzer, S.;Sheffield, D.;Somalwar, S.;Stone, R.;Thomas, S.;Thomassen, P.;Walker, M.;Foerster, M.;Riley, G.;Rose, K.;Spanier, S.;York, A.;Bouhali, O.;Hernandez, A. C.;Celik, A.;Dalchenko, M.;De Mattia, M.;Delgado, A.;Dildick, S.;Eusebi, R.;Gilmore, J.;Huang, T.;Kamon, T.;Krutelyov, V.;Krutelyov, V.;Mueller, R.;Osipenkov, I.;Pakhotin, Y.;Patel, R.;Perloff, A.;Rose, A.;Safonov, A.;Tatarinov, A.;Ulmer, K. A.;Akchurin, N.;Cowden, C.;Damgov, J.;Dragoiu, C.;Dudero, P. R.;Faulkner, J.;Kunori, S.;Lamichhane, K.;Lee, S. W.;Libeiro, T.;Undleeb, S.;Volobouev, I.;Appelt, E.;Delannoy, A. G.;Greene, S.;Gurrola, A.;Janjam, R.;Johns, W.;Maguire, C.;Mao, Y.;Melo, A.;Ni, H.;Sheldon, P.;Snook, B.;Tuo, S.;Velkovska, J.;Xu, Q.;Arenton, M. W.;Cox, B.;Francis, B.;Goodell, J.;Hirosky, R.;Ledovskoy, A.;Li, H.;Lin, C.;Neu, C.;Sinthuprasith, T.;Sun, X.;Wang, Y.;Wolfe, E.;Wood, J.;Xia, F.;Clarke, C.;Harr, R.;Karchin, P. E.;Don, C. K. K.;Lamichhane, P.;Sturdy, J.;Belknap, D. A.;Carlsmith, D.;Cepeda, M.;Dasu, S.;Dodd, L.;Duric, S.;Gomber, B.;Hall-Wilton, R.;Herndon, M.;Herve, A.;Klabbers, P.;Lanaro, A.;Levine, A.;Long, K.;Loveless, R.;Mohapatra, A.;Ojalvo, I.;Perry, T.;Pierro, G. A.;Polese, G.;Ruggles, T.;Sarangi, T.;Savin, A.;Sharma, A.;Smith, N.;Smith, W. H.;Taylor, D.;Woods, N.;Collaboration, C. M. S.
Keywords: Double Parton Scattering; Cross-Sections; Pythia; Collisions; Physics